2020
DOI: 10.3390/microorganisms8091317
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Characterization of Antimicrobial Resistance and Virulence Genes of Coagulase-Negative Staphylococci from Wild Birds in Spain. Detection of tst-Carrying S. sciuri Isolates

Abstract: The objective of this study was to determine the prevalence and diversity of coagulase-negative staphylococci (CoNS) species from wild birds in Spain, as well as to analyze the antimicrobial resistance phenotype/genotype and the virulence gene content. During 2015–2016, tracheal samples of 242 wild birds were collected in different regions of Spain for staphylococci recovery. The species identification was performed using MALDI-TOF. The antimicrobial resistance phenotype and genotype was investigated by the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 41 publications
(80 reference statements)
5
37
1
1
Order By: Relevance
“…The reason for this low data has not been fully elucidated. However, it appeared that S. aureus is not often the staphylococcal species associated with the nasotracheal carriage in wild birds (excluding birds of prey) [ 52 ]. Moreover, it could be that most of the studied birds had a feeding lifestyle that seldom allows S. aureus carriage, as in the case of birds that feed in the natural or semi-natural environment as opposed to those that feed close to landfills [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this low data has not been fully elucidated. However, it appeared that S. aureus is not often the staphylococcal species associated with the nasotracheal carriage in wild birds (excluding birds of prey) [ 52 ]. Moreover, it could be that most of the studied birds had a feeding lifestyle that seldom allows S. aureus carriage, as in the case of birds that feed in the natural or semi-natural environment as opposed to those that feed close to landfills [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Ruiz-Ripa et al [ 52 ], about 48.8% of storks showed S. sciuri tracheal carriage. However, Gómez et al [ 37 ] reported as high as 34.8% S. aureus carriage in white stork nestlings exposed to human residues.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CoNS are being increasingly studied within veterinary medicine, while their role as disease-causing pathogens in animals is still regarded as small. Although the relevance for human disease is not fully established, it has been shown that CoNS-inhabiting animals can display a wide range of antimicrobial resistances, and thus may potentially serve as a reservoir of resistance genes [ 20 ].…”
Section: Increasing Clinical Impact Of Consmentioning
confidence: 99%
“…In particular, the genes coding for PVL and exfoliative toxins, important factors in humans skin colonization and infection [ 33 , 34 ], were not detected. Though these virulence factors can be found in animal or environmental strains, they are generally associated with human clinical pathogens and rarely detected in staphylococci of veterinary origin [ 56 , 57 , 58 ]. For these reasons, it could be supposed that the investigated isolates were not of human origin.…”
Section: Discussionmentioning
confidence: 99%
“…Only one S. aureus strain harbored the gene for the toxic shock syndrome toxin. This superantigen strongly favorites staphylococcal infection, but its detection in animal staphylococci is very variable [ 16 , 56 , 58 , 59 ]. In the present study, the investigated genes were selected on the basis of available information reported in recent publications, the site of infection, bacterial species, and zoonotic implications.…”
Section: Discussionmentioning
confidence: 99%